Retrospective study of degenerative mitral valve disease in small-breed dogs: survival and prognostic variables - Kim, Hyun-Tae; Han, Sei-Myoung; Song, Woo-Jin; Kim, Boeun; Choi, Mincheol; Yoon, Junghee; Youn, Hwa-Young (Journal of veterinary science (Suwŏn-si, Korea), 2017)
Small-breed dogs (n = 168; weight ＜ 15 kg) diagnosed with myxomatous mitral valve degeneration based on a routine clinical examination, radiology, electrocardiography, and echocardiography at the Seoul National University Veterinary Medical Teaching Hospital were included in this study. Survival periods were determined, and there were significant differences in survival rates among the three International Small Animal Cardiac Health Council classes. The mean follow-up period was 14.3 ± 12.1 months. Univariate analysis revealed that dyspnea, pulmonary edema, and vertebral heart score were significantly associated with survival time ( ＜ 0.05). Additionally, age, left atrial-to-aortic root ratio, ejection fraction, and left ventricular end diastolic volume were associated with an increased risk of death ( ＜ 0.1), while body weight, body condition score, systolic blood pressure, arrhythmia, syncope, fractional shortening, and end systolic volume were not associated with an increased risk of death. These results suggest that among the assessed variables dyspnea, pulmonary edema, and vertebral heart score could be useful prognostic factors for providing patient information to owners.